Transoral laser microsurgery ± adjuvant therapy versus chemoradiotherapy for stage III and IVA oropharyngeal squamous cell carcinoma: Preliminary comparison of early swallowing outcomes. Issue 10 (9th February 2015) - O'Hara, James; Cosway, Benjamin; Muirhead, Colin; Leonard, Nicola; Goff, Diane; Patterson, Joanne
Abstract: Background: Observational data suggests transoral surgery may offer benefit in swallowing over chemoradiotherapy. Methods: In this preliminary, non‐randomized study, patients with stage III and IVA oropharyngeal carcinoma treated with transoral laser microsurgery (TLM) were assessed pretreatment and 3 months after treatment using the MD Anderson Dysphagia Inventory (MDADI), the Performance Status Scale (PSS), and a timed Water Swallow Test (WST). Comparisons were made with a historical chemoradiotherapy (CRT) cohort. Results: Based on patients with measurements at both times, the decrease in score between baseline and 3 months was greater for CRT patients ( n  = 26–28) than for TLM ( n  = 20–21) patients for each of MDADI, PSS, and WST. A repeated measures analysis that looked at all 3 scores simultaneously and allowed for missing values gave mostly similar results (except for MDADI). Conclusion: TLM was associated with good early swallowing outcomes at 3 months and may offer a benefit over CRT. The results should be viewed as preliminary data, providing useful reference for any proposed controlled trial. © 2015 Wiley Periodicals, Inc. Head Neck 37: 1488–1494, 2015